GEOLOGICAL AND ECONOMIC CRITERIA OF INDUSTRIAL VALUE OF COAL DEPOSITS WITH INSIGNIFICANT RESERVES - Kurylo, M.; Bala, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of this study is to analyze and systematize criteria by which, in domestic and international practice, the industrial value of coal deposits with small and insignificant reserves is determined. The analysis and systematization of such factors in general for all coal deposits with the definite definition of the most influential characteristics for small stocks are carried out. Mining and geological factors, which are caused by natural characteristics of the deposit and directly related to the concrete object, are determined, and there have been singled out factors concerning the minerals in general or characterizing the external conditions of industrial development of deposits. For coal deposits with insignificant reserves, the criteria that directly affect the most critical parameter - the value of coal reserves and, consequently, the lifetime of the mining enterprise have paramount importance. Such criteria are the quality of coal, which defines the direction of use and its liquidity, the degree of geological study, which expresses the geological risks of reserves confirmation, and the complexity of mining technical conditions that define methods and systems for the reserves disclosure and development. In general, external factors for coal deposits are most affected by the availability of raw material substitutes and market conditions, and coal prices. For deposits with insignificant reserves, prices and possibility of mining, which involves availability of licenses and social permits, may have a greater impact. Industrial significance of deposit with insignificant reserves may appear favorable of all other conditions of development - mining and technical conditions that form low cost of production, coal quality, favorable market conditions for mineral raw materials, localization of the deposit near consumers, etc. At the same time, the main prerequisite for attracting objects with insignificant reserves to exploitation should be their high degree of geological study. Decision about possible industrial significance should be taken after detailed technical and economic calculations.
Keywords: industrial significance; insignificant coal reserves; evaluation criteria